2018
DOI: 10.3892/or.2018.6574
|View full text |Cite
|
Sign up to set email alerts
|

NFIB promotes cell growth, aggressiveness, metastasis and EMT of gastric cancer through the Akt/Stat3 signaling pathway

Abstract: Nuclear factor I/B (NFIB) plays a crucial role in the progression of several types of cancers. However, its role in gastric cancer (GC) remains unclear. The present study revealed that NFIB was highly expressed in GC tissues and was positively associated with the clinicopathological features of GC patients. Downregulation of NFIB inhibited the tumor growth, migration and aggression of MKN45 and HGC27 cells in vitro. In addition, NFIB expression promoted epithelial‑mesenchymal transition (EMT), which was accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 26 publications
5
32
0
Order By: Relevance
“…NFIB is a member of the nuclear factor family (which also includes NFIA, and NFIX). Emerging evidence has demonstrated that NFIB could not only participate in normal somatic development [22], it also acted as an oncogene and involved in tumorigenesis of several cancers, including osteosarcoma [23], glioma [24], astrocytoma [25], gastric cancer [26], breast cancer [27]. Liu et al's research showed that NFIB could suppress p21 transcription [28].…”
Section: Discussionmentioning
confidence: 99%
“…NFIB is a member of the nuclear factor family (which also includes NFIA, and NFIX). Emerging evidence has demonstrated that NFIB could not only participate in normal somatic development [22], it also acted as an oncogene and involved in tumorigenesis of several cancers, including osteosarcoma [23], glioma [24], astrocytoma [25], gastric cancer [26], breast cancer [27]. Liu et al's research showed that NFIB could suppress p21 transcription [28].…”
Section: Discussionmentioning
confidence: 99%
“…After the EMT process, cells lose polarity and acquire the ability to move freely . Previous studies have reported that NFIB can induce EMT, however, the specific mechanism is still unclear . In our study, we explored the link between NFIB and EMT‐TFs and discovered that NFIB could promote snail expression by binding to the Snail promoter.…”
Section: Discussionmentioning
confidence: 89%
“…NFIB was reported to bind to the EZH2 promoter and promote EZH2 expression, which could activate the PI3K/AKT pathway . Wu et al discovered that NFIB can activate the Akt/Stat3 signaling pathway in gastric cancer. However, the relationship between the effects of NFIB on the biological behavior of CRC and the activation of the Akt pathway has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, western blot analyses revealed that CRP significantly elevated extracellular signal-regulated kinases (ERKs) levels and IL-6 notably elevated signal transducer and activator of transcription 3 (STAT3) levels [36]. Therefore, researchers stated that CRP activates MAPK/ERK pathway and IL-6 activates Akt/STAT3 pathway were both strongly associated with carcinogenesis [37][38][39][40]. ERKs have a pleiotropic effect on neoplasms where they activate pro-survival pathways leading to cell proliferation and migration, modulate apoptosis, cell differentiation and senescence and according to research by Salaroglio et al ERKs this plays a major role in tumor resistance for immune system responses and chemotherapy [37].…”
Section: Increased Crp As a Bad Prognostic Sign -Potential Mechanismmentioning
confidence: 99%